The impact of integrated crop-livestock systems : a review of the components and barriers of the classic farming approach - Prather, Alison (Kansas State University, 2022)
Integrated crop-livestock systems (ICLS) are designed to utilize cover crops, livestock, and cash crops in a sustainable cycle. Existing in agriculture for 8 to 10 millennia, ICLS are beginning to make a comeback in the global effort to make agriculture practices environmentally conscious and sustainable. Research has documented benefits for farm production in weed management, animal performance, crop yield, and diversity through ICLS implementation. The environment benefits from nutrient cycling, methane emission mitigation, and holistic climate resiliency of the farm. Economic strength and prosperity are staples of ICLS through diversified income, risk management, and reduced use of costly additive crop inputs. Barriers do exist for the adoption of ICLS due to gaps in knowledge and research but bolstering by political and social resources to close the gaps can make ICLS a reality for any farmer. This report will examine the benefits, consequences, and barriers of implementing ICLS.
Keywords: Integrated crop-livestock system